Interfacing Polymers and Tissues: Quantitative Local Assessment of the Foreign Body Reaction of Mononuclear Phagocytes to Polymeric Materials. Issue 4 (30th March 2017) - Giusto, Elena; Donegà, Matteo; Dumitru, Andra C.; Foschi, Giulia; Casalini, Stefano; Bianchi, Michele; Leonardi, Tommaso; Russo, Alessandro; Occhipinti, Luigi G.; Biscarini, Fabio; Garcia, Ricardo; Pluchino, Stefano
Abstract : A quantitative method to assess the in vitro foreign body reaction (FBR) of mononuclear phagocytes (MP) to polymers relevant in implants for prosthetics, advanced therapies, and regenerative medicine is presented. It integrates single‐cell force spectroscopy (SCFS) with immunogenic profiles of the MPs. In cell force spectroscopy experiments a single phagocyte, linked at the end of an atomic force microscopy cantilever, probes the adhesion forces between the cell and the polymer surface. SCFS measures adhesion forces in a range from 10 pN to 100 nN and with spatial resolution from cell size down to nanometers, accessing the early adhesion events established at contact times between milliseconds and minutes. The time evolution within the first 60 s of the adhesion force between the phagocyte and the polymer surface before and after the treatment with an immunosuppressive drug, viz. Minocycline, a Federal Drug Administration (FDA)‐approved third generation tetracycline with anti‐inflammatory effects, is then studied. The adhesion force values measured at the single cell level is shown to correlate to the immunogenic profiles obtained by analysis of biomarkers and morphology of the MPs in culture. Also, Minocycline causes a decrease of both proinflammatory gene expression profiles and adhesive forces of single cells. Abstract : Polymers relevant for biomedical applications are screened for their ability to induce foreign body reaction (FBR) in vitro by a new quantitative local approach. Adhesion force by single‐cell force spectroscopy (SCFS) is correlated to the expression of inflammatory biomarkers and morphology. The results also show that the anti‐inflammatory drug Minocycline decreases the adhesion of macrophages on immunogenic poly‐lactic‐ co ‐glycolic acid (PLGA), preventing their activation to FBR.